Quantification of Impacts on the Transport Serviceability at the Loss of Functionality of Significant Road Infrasturucture Objects - Leitner, Bohus; Luskova, Maria; O’Connor, Alan; van Gelder, Pieter (Communications - Scientific letters of the University of Zilina, 2015)
Incidents and unexpected phenomena occurrence in transport significantly affect the performance and capacity parameters of traffic infrastructure and its important objects. The objective of this article is to indicate possible uses of software tools to model the traffic at the loss of functionality of potential elements of critical road infrastructure and to demonstrate the possibility of their efficient use. The conducted case study applied the simulation models for quantification of the infrastructure traffic load under standard conditions as well as during the constraint of the transport system operation, i.e. after implementation of restrictive conditions (e.g. considering shutdown of an important bridge). The solution of the situation at the shutdown of an important element of infrastructure is possible to be designed, verified and modified using appropriately devised adequate virtual models. By this means, it is possible to predict the significance of the shutdown – criticality and influence of the loss of the functionality considering the transport serviceability parameters of the road infrastructure in the affected area.